Deskripsi Perwujudan Budaya Peduli Lingkungan di SDN 06 Pontianak Timur - Sagita, Sherli Gebby (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the embodiment of an environmental care culture at SDN 06 East Pontianak with a research focus, namely the realization of an environmental care culture with four adiwiyata components, namely, environmentally friendly policies, the implementation of environment-based curriculum, participatory-based environmental activities, and the management of environmentally friendly supporting facilities. The research method used is a qualitative method of descriptive type with data collection techniques for interviews, observations, and documentation. The subjects in this study were the principal, teachers, adiwiyata coordinators, 3 grade IV students and 3 grade V students. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the research on the realization of a culture of environmental care at SDN 06 East Pontianak are realized through the adiwiyata program, namely school residents must have insight into the environment starting from the preparation of the school's vision, mission and goals which contain environmental management, implementing an environment-based curriculum in learning, carrying out participatory-based activities, and managing environmentally friendly supporting facilities that have been provided by the school